1991
DOI: 10.1073/pnas.88.23.10740
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the activation of Hageman factor (factor XII) by human vascular endothelial cell culture supernates.

Abstract: The supernatant fluid (conditioned medium) of cultured human vascular endothelial cells inhibits activation of Hageman factor (factor XII), whether by ellagic acid, bovine brain sulfatides, or bismuth subgallate; inhibition appears to be a property of one or more proteins in the culture supernates.This phenomenon may contribute to maintaining the fluidity of circulating blood by inhibiting surface activation of the intrinsic pathway of coagulation.Circulating blood remains unclotted despite contact with the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These data suggest that FXII auto-activation is not a physiologic phenomenum. The lack of FXII activation following incubation on HUVEC may be due to a HUVEC secreted substance reported to inhibit FXII activation on artificial negatively charged surfaces (29,30). This unidentified substance may be identical to the agent reported to inhibit FXII activation by ellagic acid in the presence of a suspension of peripheral blood mononuclear cells, monocytes, T or B lymphocytes, platelets, granulocytes, eosinophils or celldepleted supernatant fluids of these suspensions (31,32).…”
Section: Discussionmentioning
confidence: 92%
“…These data suggest that FXII auto-activation is not a physiologic phenomenum. The lack of FXII activation following incubation on HUVEC may be due to a HUVEC secreted substance reported to inhibit FXII activation on artificial negatively charged surfaces (29,30). This unidentified substance may be identical to the agent reported to inhibit FXII activation by ellagic acid in the presence of a suspension of peripheral blood mononuclear cells, monocytes, T or B lymphocytes, platelets, granulocytes, eosinophils or celldepleted supernatant fluids of these suspensions (31,32).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, it has been demonstrated that factor XI1 bound to endothelial cells may become gradually autoactivated during a two hour interval (244). However, other studies have shown that both conditioned medium and lysates of human umbilical vein endothelial cells contain substances that impair the formation of factor XIIa when activated by different active surfaces (245,246). Partial purification of the inhibitory fraction from the cell lysates has revealed a protein of 22.5 kDa, which was different from other intrinsic coagulation inhibitors (246).…”
Section: Endotheli~irn and Factor XIImentioning
confidence: 91%
“…Inhibitory activity has also been found in normal human plasma [ 161, and in several plasma constituents, including the C Iq subcomponent of the first component of complement (C 1) [ 171, and P,-glycoprotein I [ 18,191, Platelet factor 4, too, inhibits activation of Hageman factor [20][21][22], These observations raise the possibility that these and similar agents may foster the fluidity of blood by interfering with initiation of the intrinsic pathway of thrombin formation. One or more such substances have been detected in the supernatant fluid of cultured human vascular endothelial cells, suggesting that these agents may have relevance to the prevention of inadvertent intravascular clotting [23].…”
Section: Discussionmentioning
confidence: 97%